Disseminated intravascular coagulation: an update on pathogenesis and diagnosis. Issue 8 (3rd August 2018) - Levi, Marcel; Sivapalaratnam, Suthesh
ABSTRACT: Introduction : Activation of the hemostatic system can occur in many clinical conditions. However, a systemic and strong activation of coagulation complicating clinical settings such as sepsis, trauma or malignant disease may result in the occurrence disseminated intravascular coagulation (DIC). Areas covered : This article reviews the clinical manifestation and relevance of DIC, the various conditions that may precipitate DIC and the pathogenetic pathways underlying the derangement of the hemostatic system, based on clinical and experimental studies. In addition, the (differential) diagnostic approach to DIC is discussed. Expert commentary : In recent years a lot of precise insights in the pathophysiology of DIC have been uncovered, leading to a better understanding of pathways leading to the hemostatic derangement and providing points of impact for better adjunctive treatment strategies. In addition, simple diagnostic algorithms have been developed and validated to establish a diagnosis of DIC in clinical practice.